Care Situation for Female Victims of Sexual Violence in Metropolitan Emergency Departments with Charité/Berlin as an Example - Hoffmann-Walbeck, H.; Möckel, M.; Etzold, S.; David, M. (Geburtshilfe und Frauenheilkunde, 2016)
of the perpetrators were friends or relations; 17 % were (ex-)partners. The waiting time in the Charité emergency departments amounted to 58 minutes on average, the medical treatment time 55 minutes. About 80 % of the personnel evaluated the “stuprum kit” as being altogether good or very good. More than ⅓ considered the time and room conditions as being unsuitable or rather unsuitable for the situation. Two thirds expressed the desire for further training and supervision. Conclusion: The structured procedure by means of the “stuprum kit” has proved its value. A need for optimisation was seen especially for the examination facilities in the emergency departments.
Keywords: sexual violence; initial treatment; stuprum kit